Lack of Desmin in Mice Causes Structural and Functional Disorders of Neuromuscular Junctions - Eiber, Nane; Fröb, Franziska; Schowalter, Mirjam; Thiel, Christian; Clemen, Christoph S.; Schröder, Rolf; Hashemolhosseini, Said (Frontiers in Molecular Neuroscience, 2020)
Desmin, the major intermediate filament (IF) protein in muscle cells, interlinks neighboring myofibrils and connects the whole myofibrillar apparatus to myonuclei, mitochondria, and the sarcolemma. However, desmin is also known to be enriched at postsynaptic membranes of neuromuscular junctions (NMJs). The pivotal role of the desmin IF cytoskeletal network is underscored by the fact that over 120 mutations of the human DES gene cause hereditary and sporadic myopathies and cardiomyopathies. A subgroup of human desminopathies comprises autosomal recessive cases resulting in the complete abolition of desmin protein. In these patients, who display a more severe phenotype than the autosomal dominant cases, it has been reported that some individuals also suffer from a myasthenic syndrome in addition to the classical occurrence of myopathy and cardiomyopathy. Since further studies on the NMJ pathology are hampered by the lack of available human striated muscle biopsy specimens, we exploited homozygous desmin knock-out mice which closely mirror the striated muscle pathology of human patients lacking desmin protein. Here, we report on the impact of the lack of desmin on the structure and function of NMJs and the transcription of genes coding for postsynaptic proteins. Desmin knock-out mice display a fragmentation of NMJs in soleus, but not in the extensor digitorum longus muscle. Moreover, soleus muscle fibers show larger NMJs. Further, transcription levels of acetylcholine receptor (AChR) genes are increased in muscles from desmin knock-out mice, especially of the AChR gamma subunit, which is known as a marker of muscle fiber regeneration. Electrophysiological recordings depicted a pathological decrement of nerve-dependent endplate potentials and an increased rise time of the nerve-independent miniature endplate potentials. The latter appears related to the fragmentation of NMJs in desmin knockout mice. Our study highlights the essential role of desmin for the structural and functional integrity of mammalian NMJs.
CRIS-Team WoS Importer:2020-11-27